Growth of Au nanoparticles on phosphorylated zein protein particles for use as biomimetic catalysts for cascade reactions at the oil–water interface. Issue 11 (24th February 2021) - Xi, Yongkang; Liu, Bo; Wang, Shuxin; Huang, Xiaonan; Jiang, Hang; Yin, Shouwei; Ngai, To; Yang, Xiaoquan
Abstract : A robust chemo- and biocatalytic cascade PIC with a recovery catalyst and a separation product was developed. The results groundbreakingly highlighted the preliminary applications of artificial enzymes and bio-enzymes in a one-pot cascade PIC. Abstract : Chemo-enzymatic cascade processes are invaluable due to their ability to rapidly construct high-value products from available feedstock chemicals in a one-pot relay manner. However, they have proven to be challenging because of the mutual inactivation of both catalysts. A conceptually novel strategy based on Pickering interfacial catalysis (PIC) is proposed here to address this challenge. This study aimed to construct a protein-stabilized Pickering system for biphasic cascade catalysis, enabled by phosphorylated zein nanoparticles (ZCPOPs) immobilized in gold nanoparticles (Au NCs). Ultra-small Au NCs, 1–2 nm in diameter, were integrated into ZCPOPs at room temperature. Then, the as-synthesized ZCPOPs–Au NCs were used to stabilize the oil-in-water (o/w) Pickering emulsion. Besides their excellent catalytic activity and recycling ability in a variety of oil phases, ZCPOPs–Au NCs possess unpredictable catalytic activity and exhibit mimicking properties of horseradish peroxidase. Particularly, the cascade reaction is well achieved using a metal catalyst and a biocatalyst at the oil–water interface. The result showed that such a combination of chemo- and biocatalysis improved the catalytic yield more than two times compared with that of sole metal catalysis. This study opened a new avenue to design nanomaterials using the combination of chemo- and biocatalysis in a Pickering emulsion system for multistep syntheses.